Left atrial appendage myxofibrosarcoma: A rare masquerader of myxoma and thrombus—"all that glitters is not gold". Issue 2 (27th December 2017) - Khan, Muhammad Shoaib; Reddy, Sahadev; Lombardi, Richard; Isabel, Pitti; Mcgregor, Walter E.; Tang, Bang; Gabriel, George; Biederman, Robert W
Abstract : Left atrial appendage mass can occasionally pose a serious challenge to physicians to identify the nature of the mass with the aid of imaging techniques. We present a case of 67‐year‐old man, who was evaluated for suspected left atria myxoma. Transesophageal echocardiography revealed a heterogeneous density originating from left atrial appendage, thought to be most consistent with a myxoma. Cardiac magnetic resonance imaging, uncharacteristically, gave an equivocal picture, suggesting the mass to be a myxoma on initial imaging and a thrombus with evidence of liquefaction necrosis following postcontrast enhancement. Surprisingly, histopathology of the mass following its surgical excision yielded a rare diagnosis of myxofibrosarcoma.